The Impact of Debt to Equity Ratio Accounting Profit and Firm Size on Price Book Value: Evidence from PT. Erajaya Swasembada Tbk (2014–2023) (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Accounting Profit, and Company Size on Price to Book Value (PBV) at PT. Erajaya Swasembada Tbk during the period 2014–2023. A quantitative approach is used by utilizing secondary data obtained from audited financial statements and stock market data. Data processing was carried out through descriptive statistics, classical assumption tests, multiple linear regression, t tests, F tests, and determination coefficient analysis using SPSS software version 25. The results showed that DER had a significant negative effect on PBV, while Company Size had a significant positive effect on PBV. In contrast, Accounting Profit does not have a significant influence on PBV. Simultaneously, the three independent variables had a significant influence on PBV with a determination coefficient value (R²) of 0.839. These findings confirm that the management of the company's capital structure and scale is an important factor in increasing the company's value in the eyes of investors. Meanwhile, fluctuations in accounting profits are not enough to significantly affect market perception. The practical implication of this research is the need for a financial strategy that focuses on the efficiency of the company's capital structure and expansion to increase the investment attractiveness and market value of the company.